Geomorfological Study on the Evaluation of Critical Land in Cepogo, Boyolali, Central Java Province - Taryono, T; Santoso, Sugiharto Budi; Priyana, Yuli (Forum Geografi, 2001)
Land is natural resources within processing needs to the wise action in order to give good returns for human and being prevented itâs conservation. In the utility of itâs land this land is proper to the agriculture land have sometime emergedthe environment problems, namely the balance of nature is disturbed. It doesnât mean that land is forbidden to use, but in the itâs utility purposes this land must be considered itâs capability or itâs balance. If form and manner of using this land doesnât disturb the natural balance, it means to be guaranted. In the countrary, if form and remain to be guaranted. In the contrary, if form and manner of using this land disregard with itâs capability, then the natural balance is disturbed, the land is called asland within dangerous condition or critical land. The coresponding problem that arises in Kecamatan Cepogo under Boyolali district on the surface level land and southern land resembles the critical land that the most erosion appearance can be found assuch sheet erosion, gully erosion, erosion in the other side, vallage forest, settlement land. Mixing estate and the infertile land. This recent exploration purpose is to understand physical factor that affects the critical land as well as to collect and to clarity the critical land. The used method is survey and laboratory analysis by land unit approach ascartography unit. The adopted data of this research is used the effectively width of soil, texture, soil permeability, soil slope, and soil appearance. From this research is understood that the explorated land has three critical land levels, namely; the medium critical land level is 4411,09 are or 17,48%, the wight critical soil level is 7909,74 are or 12,86% of the whole exploration area wide.